(untitled) (Revista Latino-Americana de Enfermagem, 2024)
Objective: to analyze the effects of a Mindfulness-based intervention on nurse leaders’ emotional intelligence and resilience. Method: a pilot study of a randomized crossover clinical trial. The sample (n=32) was randomized into Group A (n=18) and Group B (n=14) and evaluated at the pre-test, post-test and follow-up moments. The outcomes were assessed using the Emotional Intelligence Measure, the Connor-Davidson Resilience Questionnaire and the Five Facet Mindfulness Questionnaire, and analyzed using Generalized Linear Mixed Models. Results: a total of 32 nurses with a mean age of 42.6 years old were evaluated. The analyses showed significant interactions between the effects of the group x moment factors on the Self-motivation (p=0.005), Sociability (p<0.001), Self-control (p=0.013), and Total (p=0.002) emotional intelligence skill scores; as well as on the Observe (p=0.042), Describe (p=0.008), Non-judgment (p<0.001), Act with awareness (p=0.004) and Total (p<0.001) mindfulness facets. Post-test: there was a statistically significant increase in the Sociability (p=0.009) and Self-control (p=0.015) emotional intelligence skills; as well as in the Non-judgment (p=0.022) and Total (p=0.002) mindfulness facets. Follow-up: a significant increase was observed in the Non-judgment (p=0.024) and Total (p=0.026) mindfulness facets. The “resilience” variable did not present statistical significance in the “group x moment” factor, both in the post-test and during follow-up. Conclusion: the Mindfulness-based intervention used proved to be effective in increasing nurse leaders’ emotional intelligence and dispositional mindfulness skills. Brazilian Registry of Clinical Trials (RBR-3c62gy), registered on March 4 th , 2020, updated on September 16 th , 2022.